Rumah Belajar Sebagai Pendorong Minat Belajar Anak Di Masa New Normal - Pertiwi Rini; Berlianti Berlianti (Smart Education, 2022)
Abstract: The Covid-19 outbreak that has hit has changed the learning system from full face-to-face to PJJ or a combination of face-to-face and distance learning or blended learning. Due to distance learning, many children, especially those in elementary school, experience a decrease in interest in learning. Therefore, the